2011
DOI: 10.4103/0255-0857.81797
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acquiring Strongyloides stercoralis infection among patients attending a tertiary hospital in south India

Abstract: In this setting, strongyloidiasis was seen more often in patients on corticosteroid therapy and with HIV infection. In HIV, an association with lower CD4 counts indicates the need for inclusion of Strongyloides as an opportunistic parasite. Gram negative sepsis was an important complication of strongyloidiasis hyperinfection in both HIV and steroid therapy. Further prospective studies on the risk of developing complicated Strongyloides infection are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…Our case report is the eighth reported case of IRIS to S. stercoralis worldwide and the first from India. Advanced HIV has not been linked with disseminated strongyloidiasis despite a 21-fold increased risk of intestinal infection in endemic areas [ 3 ]. Few previous reports from India have shown that the prevalence of S. stercoralis in HIV-infected patients ranged from 0% to 27.3% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our case report is the eighth reported case of IRIS to S. stercoralis worldwide and the first from India. Advanced HIV has not been linked with disseminated strongyloidiasis despite a 21-fold increased risk of intestinal infection in endemic areas [ 3 ]. Few previous reports from India have shown that the prevalence of S. stercoralis in HIV-infected patients ranged from 0% to 27.3% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced HIV has not been linked with disseminated strongyloidiasis despite a 21-fold increased risk of intestinal infection in endemic areas [ 3 ]. Few previous reports from India have shown that the prevalence of S. stercoralis in HIV-infected patients ranged from 0% to 27.3% [ 3 ]. However, cases of SHS have been rarely described in HIV-infected patients in India [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive association between S. stercoralis infection and type 2 diabetes mellitus (T2DM) has been reported in Brazil (4) but a study performed in India suggested a negative relationship between these conditions (5). A study conducted by Hays et al, provides some evidence that chronic infection with S. stercoralis may protect against the development of T2DM in humans (6).…”
Section: Introductionmentioning
confidence: 99%
“…HIV infection was most commonly associated with strongyloidiasis in our study, which was in concordance with another study from our country. [3] Increasing number of cases with strongyloidiasis reported in transplant settings has encouraged recommendations for a pretransplant screening. [4] The mean number of larvae detected from the samples of immunosuppressed versus immunocompetent patients was 21.7/cover slip area and 2.9/cover slip area, respectively.…”
mentioning
confidence: 99%